Efecto de la aplicación de enmiendas orgánicas, como complemento a la fertilización química en la producción de pimiento (Capsicum annum L.), en la zona de Babahoyo - Barbotó, Víctor Molina; Paredes, Joffre León; Betancourt, Ricardo Chávez; Alvarado, Darío Dueñas; Jiménez, Eduardo Yance; Arias, David Mayorga; Vargas, Pedro Rodríguez; Hurtado, William Filian; Ochoa, Juan Salina; Campozano, Cristina Maldonado (European Scientific Journal, ESJ, 2017)
Pepper (Capsicum annum l.) belongs to the genus Capsicum of the Solanaceae families. Its fruit is green. It has a high content of vitamins A and C. This fruit, however, is of great importance to the human population. The stud of pepper (Capsicum annuum l.) was carried out in the fields located in the Technical University of Babahoyo, Faculty of Agricultural Sciences in Los Ríos province, Ecuador. This work was carried out between the months of September to January 2016. The planting was done with the hybrid material, Salvador, in plots of 11.9 m2. The statistical design used was completely randomized blocks with 10 treatments and 4 replicates. The useful area of the plot was 476 m2. At the end of the crop cycle, the following was obtained: plant height, days to flowering, days to harvest, number of fruits per plant, fruit length, weight of fruit, fruit diameter, size of fruit, days to maturity, yield, and cost-benefit ratio. Based on the results of the present study, it was demonstrated that the application of organic matter in combination of a fertilization program affected the agronomic performance of the cultivation of peppers under the field conditions in which it was developed. Based on statistical analysis, we can also mention thatSalvador hybrid material used in this trial presents an extension in the days corresponding to the flowering and ripening under the applications of functional organic material. This factor coupled with the application of chemical fertilizer affects performance. The best agronomic performance of the fruit was found in treatment, Bokashi 4000 Kg / ha, which presented the best features based on the number of fruits, fruit diameter, and length off. As a result of the application of fertilizers and amendments, it was found that they had influence on the plant height measurements made in the evaluated treatments.